Pengaruh Media Pembelajaran Berbasis Aplikasi Canva terhadap Hasil Belajar Pendidikan Agama Islam - Achmad Syarifudin (Jurnal Ilmiah Edukatif, 2023)
The research aims to determine how much influence the application of learning media based on the Canva application has on the Islamic Religious Education learning outcomes of class VII students at SMP Negeri 2 Putussibau. The research method uses quantitative with an experimental approach as a Quasi-Experimental with Nonequivalent Control Group Design. The subjects of this research consisted of 2 classes, namely class VIIA as the control class and class VIIB as the experimental class, totaling 58 people. Sampling was done by purposive sampling or based on specific objectives for equality between the two types. The data collection techniques used are observation, tests, and documentation. The results of this research are that the research learning outcomes in the experimental class obtained an average of 85.68, while the control class obtained an average of 79.31. Based on the hypothesis test, the value of count was 4.584 > Table 2.003, so it could be said that there was a significant influence by implementing learning media based on the Canva application compared to using Microsoft PowerPoint learning media